Fresh fruits, vegetables, and dairy products : India's potential for export to other Asian countries. - Export-Import Bank of India ([Mumbai] : Quest Publications, 2005)
On fruit trade, vegetable trade, and dairy products export marketing from India; a study.
Keywords: Fruit trade -- India; Vegetable trade -- India; Dairy products -- India; Export marketing -- India